Environmental Health Risk Assesement in Flood-prone Area in Tamangapa Sub-District Makassar. (May 2018) - Haris, Ibrahim Abdul; Basir, Basir
Abstract: Environmental health in Indonesia is still caution to concern, poor sanitation in Indonesia is characterized by the high incidence of infectious diseases in society. The society in flood-prone area has a high-risk exposure on the disease based on the environment because they live in disaster-prone area. This research aimed to describe the condition of sanitary facilities and risky behavior on public health in flood-prone areas in Manggala district particularly in Tamangapa sub-district of Makassar. This reserach uses an observation method with a descriptive approach. The data is processed by using SPSS and Arc View GIS applications. Environmental risk category is determined by the approach of Environmental Health Risk Assessment (EHRA). The results showed that the flood-prone area in RT 04 RW 06 was included in very high-risk category at 229 with an index value of environmental health risks 212-229. Meanwhile, RT 04 RW 05 was in the category of low risk in the amount of 155 with an index of 155-173. Environmental health hazards identified in Tamangapa flood-prone areas sub-district includes domestic sources of clean water, domestic wastewater, and household garbage.